(untitled) ("Journal "U". Economy. Management. Finance.", 2026)
The article presents an econometric analysis of the impact of the minimum wage and inflation on employment in the Russian Federation. Based on data for 2010–2026, a regression model reveals that an increase in the real minimum wage restrains labor demand, while inflation partially compensates for this effect.